Desempenho e características de carcaça de dois biótipos de ovinos da raça Santa Inês terminados a pasto e suplementados com blocos multinutricionais - Lira, Aianne Batista (2016)
This study aimed to evaluate the performance characteristics and sheep carcass St. Agnes finished on pasture and supplemented with multinutrient blocks. 20 whole lambs, 10 Santa biotype traditional and modern Ines Santa Ines 10. These were distributed in a completely randomized design, where they remained until they reach the age at slaughter of 264 days were used. Despite having different biotypes, the sheep were not statistically different for the performance variables, quantitative, qualitative, morphometry, biometrics, only equity palette biotype was higher than 19.75%, while for the traditional was 19, 18%. There was a higher consumption of multinutritional block for the flock up to 56 days of experiment, peaking at 0.240 g / animal / day, but at 84 days there was a decline of 0,198g / animal / day. The average daily weight gain (ADG) was 144.22 and 146.67 for the traditional and modern biotype, respectively, and the final weight (PF) was 32.26 and 32,66kg for each biotype. The animal carcass classification is moderate, and hence a thin substrate. The gross profit margin was 78 reais / animal. Despite the differences biotípicas sheep Santa Inês finished on pasture and supplemented with multinutrient blocks have carcasses with similar characteristics.